PENGARUH BRAND IMAGE DAN BRAND AMBASSADOR TERHADAP KEPUTUSAN PEMBELIAN PRODUK KOSMETIK GLAD2GLOW - Rahma, Nur Luthfiah Yulia; Sudarwanto, Tri (Jurnal Pendidikan Tata Niaga (JPTN), 2024)
This study aims to determine the effect of brand image and brand ambassador on purchasing decisions for Glad2glow cosmetic products. This type of research uses quantitative research. The population in this study are all consumers who buy or use Glad2glow, the number of which is not known with certainty. The sample used was 100 people using purposive sampling technique and using the Lameshow formula. Data collection using a questionnaire through Google Form with data analysis techniques using multiple linear regression analysis, in this study using the SPSS version 26 program. The results of this study indicate that the brand image variable (X1) and the brand ambassador variable (X2) have an effect on purchasing decisions (Y).